2012
DOI: 10.1155/2012/386410
|View full text |Cite
|
Sign up to set email alerts
|

Development of Class IIa Bacteriocins as Therapeutic Agents

Abstract: Class IIa bacteriocins have been primarily explored as natural food preservatives, but there is much interest in exploring the application of these peptides as therapeutic antimicrobial agents. Bacteriocins of this class possess antimicrobial activity against several important human pathogens. Therefore, the therapeutic development of these bacteriocins will be reviewed. Biological and chemical modifications to both stabilize and increase the potency of bacteriocins are discussed, as well as the optimization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 117 publications
1
71
0
Order By: Relevance
“…In the media where every salt was tested separately, the best results were achieved with KCl, MgCl 2 or MnSO 4 , the activity in supernatant during the growth was increased up to 160 AU/ml. The same results were observed in the medium that was supplemented with all 8 salts or in After testing all salts and combinations of it in this work, the highest bacteriocin activity was achieved in media supplemented combining KCl and MgCl 2 or CaCl 2 and ZnSO 4 or MnSO 4 and NaHCO 3 . In this case the highest activity during the growth in these modified media was increased up to 320 AU/ml.…”
Section: Growth Medium Optimization For Higher Cell Growth and Bactersupporting
confidence: 82%
See 3 more Smart Citations
“…In the media where every salt was tested separately, the best results were achieved with KCl, MgCl 2 or MnSO 4 , the activity in supernatant during the growth was increased up to 160 AU/ml. The same results were observed in the medium that was supplemented with all 8 salts or in After testing all salts and combinations of it in this work, the highest bacteriocin activity was achieved in media supplemented combining KCl and MgCl 2 or CaCl 2 and ZnSO 4 or MnSO 4 and NaHCO 3 . In this case the highest activity during the growth in these modified media was increased up to 320 AU/ml.…”
Section: Growth Medium Optimization For Higher Cell Growth and Bactersupporting
confidence: 82%
“…Combination of MgCl 2 with KCl can be even better that using MgCl 2 only. The best growth was achieved in NB medium supplemented only with MnSO 4 . Growth media components were identified that may increase better bacteriocin production in Geobacillus stearothermophilus 15 strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a variety of administration methods have been proven successful, such as subcutaneous, intravenous, intranasal, intragastric, intraperitoneal, and topical, their efficacies have not yet been directly compared (Jabes et al 2011;Lohans & Vederas 2012). Moreover, some of these methods are unnecessarily invasive (Lohans & Vederas 2012).…”
Section: Bacteriocin Application and Prospectsmentioning
confidence: 99%